Unified Solutions of Energy-Momentum-Squared Gravity - Keskin, Ali İhsan (AMER INST PHYSICS, 2018)
In this study, we realize a unified solution of F(R, T-2) gravity in the context of the spatially flat Friedmann-Robertson-Walker universe, where R is the Ricci curvature scalar and T-2 = T mu nu T mu nu is the scalar constructed from the square of the energy-momentum tensor. We observe that these solutions describe a transition from deceleration eras of the universe to late-time quintessential dark energy in a unified form.
Keywords: INFLATIONARY UNIVERSE; FLATNESS; HORIZON